2015
DOI: 10.1186/s12885-015-1117-0
|View full text |Cite
|
Sign up to set email alerts
|

A functional in vitro model of heterotypic interactions reveals a role for interferon-positive carcinoma associated fibroblasts in breast cancer

Abstract: BackgroundCancer-associated fibroblasts (CAFs) play an important role in breast cancer pathogenesis by paracrine regulation of breast cancer cell biology. Several in vitro and mouse models have characterized the role of cell contact and cytokine molecules mediating this relationship, although few reports have used human CAFs from breast tumors.MethodsPrimary breast CAF cultures were established and gene expression profiles analysed in order to guide subsequent co-culture models. We used a combination of colori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…CAFs can be isolated from various cancer types such as breast cancer, prostate cancer, pancreatic cancer, cholangiocarcinoma, lung cancer, gastric cancer, and colorectal cancer. However, CAFs are relatively rare in brain, renal, and ovarian cancers [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Characteristics Of Cafsmentioning
confidence: 99%
“…CAFs can be isolated from various cancer types such as breast cancer, prostate cancer, pancreatic cancer, cholangiocarcinoma, lung cancer, gastric cancer, and colorectal cancer. However, CAFs are relatively rare in brain, renal, and ovarian cancers [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Characteristics Of Cafsmentioning
confidence: 99%
“…However, CAFs are actually defined as an assembly of heterogeneous mesenchymal cells, whose function may be different from resident tissue fibroblasts . Cancer‐associated fibroblasts have been isolated from various tumours, such as prostate cancer, lung cancer, breast cancer, gastric cancer, colorectal cancer and pancreatic cancer, whereas CAFs are relatively rare in brain cancer, ovarian cancer and kidney cancer . Interactions between cancer cells and the tumour microenvironment (TME) are well known to contribute to the outcome of tumours.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the secretome of cancer cells and its impact on therapy response has gained attention and numerous studies explore its role in several aspects of tumour including in which compartment of the tumour this pathway is activated. Moreover, high expression of interferon-regulated genes in several tumour entities also strongly correlated with a worse outcome in patients 37,38 . All of these studies highlight the high degree of plasticity of type I IFN and the need for a better understanding of the role of this pathway in the context of cancer.…”
Section: Discussionmentioning
confidence: 95%
“…identified in breast cancer a subset of fibroblasts characterized by a type I IFN response and showed that high expression of certain interferon stimulated genes in patient samples correlated with patient outcome 37 . In our study we show that cancer cells exposed to chemotherapeutic agents upregulate the expression of type I IFN, namely IFNb1.…”
Section: Discussionmentioning
confidence: 99%